2011
DOI: 10.5012/jkcs.2011.55.6.960
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of N-[2-(aryl/substituted aryl)-4-oxo-1,3-thiazolidin-3-yl]pyridine-4-carboxamide

Abstract: ABSTRACT. A series of isonicotinyl hydrazones and their 4-thiazolidinones have been synthesized by condensation of isonicotinic acid hydrazide with various aromatic aldehydes to yield Schiff's bases, followed by the cyclocondensation of Schiff's bases with 2-mercaptoacetic acid to yield their 4-thiazolidinones. The synthesized compounds have been characterized by their elemental, analytical and spectral studies. All these compounds were evaluated for their invitro antimicrobial activity against a spectrum of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Compound 2d showed outstanding inhibition against Pseudomonas aeruginosa, with an IC 50 value 29.7 µg/mL, whereas compounds 2a-c, 2e-f, 2h-j exhibited mild to average activity against Pseudomonas aeruginosa. From the screening data, it was observed that electron withdrawing and donating groups on the aryl ring had a substantial influence on the antibacterial activities, confirming earlier reports that on the antibacterial activity of various aryl thiophene derivatives bearing electron donating and electron withdrawing groups [14,16,22]. It was previously claimed that the antibacterial activity of compounds containing electron withdrawing groups was more potent against Gram-negative bacteria.…”
Section: Chemistrysupporting
confidence: 82%
See 1 more Smart Citation
“…Compound 2d showed outstanding inhibition against Pseudomonas aeruginosa, with an IC 50 value 29.7 µg/mL, whereas compounds 2a-c, 2e-f, 2h-j exhibited mild to average activity against Pseudomonas aeruginosa. From the screening data, it was observed that electron withdrawing and donating groups on the aryl ring had a substantial influence on the antibacterial activities, confirming earlier reports that on the antibacterial activity of various aryl thiophene derivatives bearing electron donating and electron withdrawing groups [14,16,22]. It was previously claimed that the antibacterial activity of compounds containing electron withdrawing groups was more potent against Gram-negative bacteria.…”
Section: Chemistrysupporting
confidence: 82%
“…Palladium-catalyzed functionalizations of thiophene derivatives have great importance due to the functional group compatibility, relative strength, low toxicity, and greater versatility of organopalladium complexes. Iqbal et al [14], Al-Adiwish et al [15], and Thomas et al [16] reported that the arylthiophene derivatives bearing electron withdrawing substituents showed excellent antibacterial activity against Gram-negative bacteria. Furthermore, Sigmundova et al [17] reported that arylthiophene derivatives with electron donating substituents exhibited potent antibacterial activity against Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotinamide derivatives, an important class of heterocyclic derivative, has attracted more and more attention in the field of pesticide due to their fungicidal activity [3-5], insecticidal activity [6-9], herbicidal activity [8,10], plant growth regulator activity [11], and bactericidal activity [12-15]. In fungicidal activity regard, some nicotinamide derivatives have been developed and commercialized, an example of such a fungicide is boscalid (Figure 1), which was discovered by BASF and registered in Britain, Germany, and Switzerland in 2004 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Nicotinamide is a water-soluble B complex vitamin which is naturally present in animal products, whole cereals and legumes [1]. Derivatives of nicotinamide have attracted much attention because of their antimicrobial [2,3,4,5,6], fungicidal [7,8,9,10,11], insecticidal [12,13] and herbicidal activity [14,15,16], plant growth regulator activity [17], cytotoxic properties [18,19], and antiangiogenesis activity [20]. Some nicotinamide derivatives, like boscalid, are used as commercial antifungicides (Figure 1).…”
Section: Introductionmentioning
confidence: 99%